If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + 2y + -6 = 11y + -10 + -5y Reorder the terms: 20 + -6 + 2y = 11y + -10 + -5y Combine like terms: 20 + -6 = 14 14 + 2y = 11y + -10 + -5y Reorder the terms: 14 + 2y = -10 + 11y + -5y Combine like terms: 11y + -5y = 6y 14 + 2y = -10 + 6y Solving 14 + 2y = -10 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 14 + 2y + -6y = -10 + 6y + -6y Combine like terms: 2y + -6y = -4y 14 + -4y = -10 + 6y + -6y Combine like terms: 6y + -6y = 0 14 + -4y = -10 + 0 14 + -4y = -10 Add '-14' to each side of the equation. 14 + -14 + -4y = -10 + -14 Combine like terms: 14 + -14 = 0 0 + -4y = -10 + -14 -4y = -10 + -14 Combine like terms: -10 + -14 = -24 -4y = -24 Divide each side by '-4'. y = 6 Simplifying y = 6
| 3y-6+y+26=5y+20-3y | | -3x-2y=-14 | | 24/3+5X4-21 | | -2x=4x-42 | | ((k-7)/5)+2=((k+8)/10) | | 24/3+5*4-21 | | v^2+4v-45= | | 1/8+a/32 | | 33.6x=70-1.4x | | 1/2(5t-7)=9/2t-(t+7/4) | | .0795t^2-.884t+1.798=0 | | -0.6x+0.5=0.1 | | 12=x+7.2 | | (2x-5)/(x-6)=0 | | x-8.8=-5.6 | | 7x+2x=x-6 | | x/4+1/2 | | 2(-8-4x)=-56 | | 3x+4y=560 | | 2(y-9)=-5y-4 | | 12.00-2x=10.00 | | 9x-2=7x | | a-2.9=-3.6 | | 28-12x/4=-8x-12/10 | | 53/5+4/5 | | 1-2.9=-3.6 | | 6.2x-4+x-1.2= | | 17-44=3(x-1)-6 | | 7j+11=14 | | 2x=4x-14.2 | | 15x-16=29+12x | | 27-3(9)+(7-4)b=24b |